Comparatismo cimarrón: un método supranacional - Croce, Marcela (Universidad Nacional del Litoral, 2019)
The article establishes the need to develop a theory and a method proposed from a Latin America stance to approach the Latin American culture, free of the models of metropolitan academies that postulate the abolition of colonialism but signify an intellectual colonization on the same object addressed.The proposal consists of a variant of comparatism that articulates the «comarcana» (regional) dimension postulated by Ángel Rama, which allows to organize segments of the continental culture and the supranational dimension both offered as a synthesis regarding transnational approaches. In addition to tracing the principles of this comparatism that deviates from the classical formulation of the method and incorporates properly Latin American theories, the text presents Brazil as a accurate example of a comparative approach to Latin America.